An appraisal of the Massachusetts Slichter Act - Treleaven, Phillips A. (Boston University, 2017)
Thesis (M.A.)--Boston University === The objective of this paper, An Appraisal of the Slichter Act, is to examine the Slichter Act of Massachusetts in order to determine whether or not it has successfully accomplished its purposes, and whether or not it is adapted to present day conditions. The evidence shows that neither of these criterion can be answered in the affirmative. Although the primary purpose of the Act, that of providing protection from industrial disputes dangerous to the public health and safety, has not been given a bona fide test, the secondary purpose of the Act of aiding the settlement of these disputes has not been realized on the basis of the existing experience. During the period of time which produced the Slichter Act, levels of strike activity were at an all time high, and a need was felt for some control of strikes. As a result, the Slichter Act, as well as similar laws in other states, was passed by the legislature. The Slichter Act provided several alternatives to handle disputes which might threaten the public health and safety by an interruption in the supply of essential goods and services, primarily food, electricity, gas, water, heat, and hospital services. The Governor was empowered to appoint a Moderator, whose function would be to induce the parties to arbitrate or otherwise reach settlement. If the Moderator was unsuccessful, the Governor was given the authority to seize the company involved, to appoint an emergency arbitration board, and finally to appoint a special commission for making recommendations. Although the recommendations of either the emergency arbitration board or the special commission were not necessarily binding, the Governor was given the power to effect such recommendations during seizure. [TRUNCATED].